DERIVATIONAL AND INFLECTIONAL MORPHEMES IN THE JAKARTA POST - dewi, tati mar (English Education:Journal of English Teaching and Research, 2019)
Many people do not know that morpheme and word are interrelated. A word can be a morpheme and can be form by combination of morphemes. More over, there are many types of morpheme with its function that affects either the sentence or the meaning. Because of the morpheme impact, writer wants to analyze about morpheme in the articles from The Jakarta Post Newspaper by its appropriatness for analyzed. Writer is going to relate to the theory from Victoria Fromkin about the types of morpheme; those are derivational and inflectional morpheme. This analyzing purposes to find out which word forming by derivational morpheme, which word forming by inflectional morpheme, how the indicated word forming, and what kind of alteration are found. Writer is going to use the descriptive qualitative method. From 6 data for derivational morpheme, writer found 8 words forming by derivational morpheme and from 8 data for inflectional morpheme, there are 29 words forming by inflectional morpheme. From the data, writer found that each morpheme has its function and impact the meaning, class of word or the grammatical function of the base word. By this paper, people are going to know how prefixes and suffixes affect the word.